1994
DOI: 10.1161/01.cir.89.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive multiple risk factor reduction on coronary atherosclerosis and clinical cardiac events in men and women with coronary artery disease. The Stanford Coronary Risk Intervention Project (SCRIP).

Abstract: Background Recent clinical trials have shown that modification of plasma lipoprotein concentrations can favorably alter progression of coronary atherosclerosis, but no data exist on the effects of a comprehensive program of risk reduction involving both changes in lifestyle and medications. This study tested the hypothesis that intensive multiple risk factor reduction over 4 years would significantly reduce the rate of progression of atherosclerosis in the coronary arteries of men and women compared with subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
340
2
23

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(374 citation statements)
references
References 49 publications
9
340
2
23
Order By: Relevance
“…Our response rate was 36%. Those who responded were likely more motivated and health conscious than nonresponders 33 ; however, emerging evidence suggests that nonresponse bias may not be a large threat to the generalizability of findings. 34 In comparison to a previous sample of 5922 CR patients at the same center, there were no differences in smoking status, marital status, or the sex ratio of our respondents.…”
Section: Limitationsmentioning
confidence: 96%
“…Our response rate was 36%. Those who responded were likely more motivated and health conscious than nonresponders 33 ; however, emerging evidence suggests that nonresponse bias may not be a large threat to the generalizability of findings. 34 In comparison to a previous sample of 5922 CR patients at the same center, there were no differences in smoking status, marital status, or the sex ratio of our respondents.…”
Section: Limitationsmentioning
confidence: 96%
“…However, the Stanford Coronary Risk Intervention Project, a multifactorial approach of low‐fat diet, smoking cessation, stress management training, and moderate exercise training, reduced cardiovascular event rates in 145 patients of the intervention group by 49% within 4 years of follow‐up. It also led to a slowed progression of atherosclerotic coronary narrowing, with a reduction in coronary lumen diameter by 0.024 mm/y in the target area, whereas a decline of 0.045 mm was evident in the control group (n=155) 96. In the Heidelberg Regression Study, a regression of coronary lesions after 1 year was only evident in patients expending >9228 kJ/wk during exercise.…”
Section: Mechanism 3: Regression Of Coronary Stenosismentioning
confidence: 98%
“…Comprehensive multifactorial rehabilitation and prevention programs have been shown to slow or partially reduce the progression of coronary atherosclerosis (3,4). Meta-analyses of studies performed in the 1970s and 1980s revealed a significant reduction in total and cardiac mortality following participation in CR (5,6).…”
Section: Efficacy Of Crmentioning
confidence: 99%